THE INFLUENCE OF MATERNAL ANXIETY TOWARDS THE SELECTION OF MATERNITY PLACES DURING COVID- 19 - Cut Yulia; Maidar Maidar; Melania Hidayat; Asnawi Abdullah; Marthoenis Marthoenis (RADJA PUBLIKA, 2022)
Corona Virus Disease (COVID-19) pandemic is currently engulfing almost the entire world, including Indonesia. As of August 12, 2021, there were 3,774,155 positive cases of Covid-19 in Indonesia, 24,709 new cases and 113,664 deaths. The group of maternal is a vulnerable group, where there are 4.9% of pregnant women who are confirmed positive for COVID-19 from 1,483 confirmed cases that have accompanying condition data. Therefore, maternal, perinatal, postpartum and newborns are vulnerable targets for transmission of COVID-19 infection and this condition is feared to increase maternal and perinatal morbidity and mortality. The general objective of this study was to determine the effect of the anxiety level of pregnant women on the choice of place of delivery during the COVID-19 period. This study used a survey method with a cross sectional approach. The study was conducted in Aceh Barat Regency, in March-June 2021. The population in this study were 637 third trimester pregnant women in 2021. The number of samples in this study was 246 samples calculated by the slovin formula and using accidental sampling technique. Data analysis used logistic regression test. The results of the bivariate analysis showed that there was a significant effect between the level of mild anxiety and the choice of place of delivery during the COVID-19 pandemic with a value (OR=5.6, 95% CI=2.04-15.3, p-value=0.001), . While the level of moderate anxiety had no significant effect on the choice of place of delivery during the Covid-19 period (OR=2.1, 95% CI=0.4-12.4, p-value=0.383) The level of severe anxiety in pregnant women was also not significant. effect on the choice of place of delivery during the Covid-19 period (OR=1.1, 95% CI=0, p-value=0.989). Expected to the government can improve education programs and supervision of the prevention and control of the Covid 19 pandemic, especially groups of pregnant women in order to minimize the possibility of excessive anxiety in pregnant women during the Covid 19 pandemic.